The Implementation of a 2/4/8 Antennas Configurable Diversity OFDM Receiver for Mobile HDTV Application - Jing Gao; Takashi Iida; Hiroyuki Mizutani; Sadanori Sakaguchi; Shuji Murakami; Atsushi Shimizu; Tomohisa Wada (International Journal of Digital Multimedia Broadcasting)
Two pre-FFT adaptive array (AA) antenna combiners and a post-FFT carrier diversity (CD) combiner are integrated with a Japan Terrestrial digital TV (ISDB-T) OFDM receiver using 90 nm 7M1P CMOS process. A 2/4/8-antenna diversity receiver can be configured and a low-cost 4 antenna diversity reception system can be realized in one LSI by making use of the AA-CD two-stage diversity combining method. Mobile reception performance is increased by 1.63 times using a denoise filter circuit and SPLINE interpolator under urban 6-path Rayleigh fading (TU6) model with 2-antenna post-FFT carrier diversity (2CD) combing mode. The die area is 49 mm2 and the power consumption is 310 mW.